2022
DOI: 10.1111/hex.13513
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the integration of smoking cessation into lung cancer screening in the United Kingdom: A qualitative study of individuals eligible to attend

Abstract: Introduction: There is limited research exploring how smoking cessation treatment should be implemented into lung cancer screening in the United Kingdom. This study aimed to understand attitudes and preferences regarding the integration of smoking cessation support within lung cancer screening from the perspective of those eligible.Methods: Thirty-one lung cancer screening eligible individuals aged 55-80 years with current or former smoking histories were recruited using community outreach and social media. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…Implementing smoking cessation interventions is likely to improve the overall effectiveness and cost effectiveness of screening programmes 42 . Individuals eligible for lung cancer screening believe the offer of smoking cessation support is acceptable and expected as part of the lung cancer screening process [43][44][45] , and attendance at screening may provide a "teachable moment"; an opportunity to inform participants of the harmful effects of smoking at a time where they may be receptive to change their behaviour [46][47][48] . Indeed, an invitation to or attendance at lung cancer screening has been shown to increase motivation for quitting and quit rates in comparison to control groups 49,50 .…”
Section: Treating Tobacco Dependency In Lung Cancer Screening Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing smoking cessation interventions is likely to improve the overall effectiveness and cost effectiveness of screening programmes 42 . Individuals eligible for lung cancer screening believe the offer of smoking cessation support is acceptable and expected as part of the lung cancer screening process [43][44][45] , and attendance at screening may provide a "teachable moment"; an opportunity to inform participants of the harmful effects of smoking at a time where they may be receptive to change their behaviour [46][47][48] . Indeed, an invitation to or attendance at lung cancer screening has been shown to increase motivation for quitting and quit rates in comparison to control groups 49,50 .…”
Section: Treating Tobacco Dependency In Lung Cancer Screening Programmesmentioning
confidence: 99%
“…Those receiving abnormal scan results appear to be particularly likely to quit smoking following engagement with lung cancer screening, with numerous studies reporting higher quit rates following an abnormal scan result or referral to a physician as compared to a normal scan result [51][52][53][54] . It has also been suggested that the provision of personalised information regarding the impact of smoking on their health may encourage uptake of lung cancer screening in those potential participants who smoke 45 .…”
Section: Treating Tobacco Dependency In Lung Cancer Screening Programmesmentioning
confidence: 99%